1990
DOI: 10.1071/ph900401
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Lasers to Collision Studies

Abstract: A review is presented of theoretical and experimental aspects of the application of lasers to the field of electron-atom collision physics. Experimental techniques are briefly reviewed and various theoretical treatments of the laser-atom interaction are dealt with in some detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The physics of multiphoton processes has generated considerable theoretical activity for carrying out very high-order perturbation calculation and to the development of nonperturbative methods. Some review papers can be found now in Refs [l]- [3]. But except for a few authors,t [4][5][6] ^ no enough attention has been paid to the investigation of quantum theory of rearrangement collision in the intense laser field.…”
Section: Introductionmentioning
confidence: 99%
“…The physics of multiphoton processes has generated considerable theoretical activity for carrying out very high-order perturbation calculation and to the development of nonperturbative methods. Some review papers can be found now in Refs [l]- [3]. But except for a few authors,t [4][5][6] ^ no enough attention has been paid to the investigation of quantum theory of rearrangement collision in the intense laser field.…”
Section: Introductionmentioning
confidence: 99%